Pengenalan Perangkat Komputer Kepada Anak-Anak Yayasan Papua Kasih Kelurahan Klawasi - Juneth N. Wattimena; Peter Manuputty; Vantri P Kelelufna (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The increasing of technology development requires that whatever is done must involve technology. One of the applications of technology is computers. The application of computers today is no longer only in official institutions or agencies but each person can have it to maximize the work done. The Computer knowledge among children who are at the Papua Kasih Foundation is still lacking. This can be because most children have never directly seen, studied, or knew in detail about computers. Thus, the service team wants to carry out an activity for children who are at the Papua Kasih Foundation so that they can find out about computer equipment. The purpose of this community service activity is to improve the development or skills of children at the Papua Cinta Foundation regarding computer equipment. The method of implementing community service activities is carried out in several stages including: field observations, preparation, and implementation of activities. Based on the service activities that have been carried out for the children at the Papua Kasih Foundation, Klawasi Village, it can be concluded that the implementation of the service activities was welcomed and enthusiastic by each participant, and using interesting methods when learning about computers could increase the interest of the participants to easy to understand.